تعزيز المعالجة الآمنة و الفعالة للاستعلامات في ظل النموذج Truman للتحكم بالوصول على المستوى الناعم - يوسف دلا; آلاء اكر (Tishreen University, 2018)
The increase in sensitive online transactions of organizations across the network has made database an important asset to the organization and thus became a target for internal and external security breaches. Due to the failure of traditional data protection systems, researchers have sought to the Fine-Grained Access Control (FGAC) model to perform this task because of its accuracy in meeting current security requirements at the level of records, columns and even individual cells. Despite the diversity of proposed FGAC methods, they are classified into two main models: Truman & Non-Truman model. The research is mainly concerned with the study of the problems resulting from the enforcing of the access control policy under the Truman model, we have concentrated on the weakness of the performance of the restricted query and studied the factors affecting it. We have improved the performance by predicate caching , and enhanced  the safe processing of queries under this model, reducing the likelihood of leakage through user-defined functions. إن تزايد التعاملات الإلكترونية للمنظمات الحساسة عبر الشبكة جعل من قواعد البيانات أحد الأصول المهمة للمنظمة ، وأصبحت بالتالي هدفاً للاختراقات الأمنية الداخلية منها والخارجية . و بسبب فشل الأنظمة التقليدية في حماية البيانات توجه الباحثون نحو نموذج التحكم بالوصول على المستوى الناعم Fine-Grained Access Control ( FGAC )  لأداء تلك المهمة وذلك لما يمتاز به من دقة في تحقيق المتطلبات الأمنية الحالية على مستوى الأسطر و الأعمدة وحتى الخلايا المفردة. وعلى الرغم من تنوع الأساليب المقترحة للنموذج FGAC فإنها تصنف إلى نموذجين رئيسيين هما Truman & Non-Truman model . قمنا بالاهتمام بشكل أساسي بدراسة المشاكل المترتبة على فرض سياسة التحكم بالوصول في ظل النموذج Truman ، و أهمها ضعف أداء الاستعلام المقيد و درسنا العوامل المؤثرة على ذلك . عملنا على تحسين الأداء عبر تخزين الشروط  ، كما عملنا على تعزيز المعالجة الآمنة للاستعلامات في ظل هذا النموذج بما يقلل من احتمالات التسرب عبر التوابع المعرفة من قبل المستخدم .